Pergamon, Türkei. Pergamon. Die Arbeiten des Jahres 2021 - Pirson, Felix (e-Forschungsberichte des DAI, 2022)
In 2021, the Pergamon excavation focused on work within the framework of the new research programme TransPergMikro. The dating of the ›Gothic Wall‹ in the 3rd century CE could be confirmed. The discovery and documentation of an imperial-period peristyle building east of the Red Hall also contribute to our knowledge of the city’s settlement history. The investigations of the amphitheatre, the theatre at the Musalla Mezarlığı, and the ›Lower Western Gymnasion‹ by archaeological building research were completed. The excavation of a Roman imperial funeral building northwest of the Asklepieion, significant new evidence for the funerary culture of Pergamon’s imperial-period elites was obtained. In the surroundings of the ancient city, the investigation of the extra-urban thermal baths was completed. The survey in the western micro-region focused on the transition zone of the eastern foothills of the Kara Dağ peninsula and the adjacent western Bakır Çay plain. In addition to the diachronic reconstruction of land use in an intensively surveyed area, surprisingly diverse settlement sites were newly discovered and documented. The investigations of sediment archives in the river plain and in Pergamon by Physical Geography were continued. The interdisciplinary rescue excavation at the Ballık cave discovered the previous year was able to confirm a temporary place of settlement and tool-production of Epipalaeolithic hunter-gatherers as well as the use of the site as a sanctuary of the goddess Meter presumably since Archaic times.